Genetic/Environmental Contributions and Immune Dysregulation in Children with Atopic Dermatitis - Chong AC; Visitsunthorn K; Ong PY (Journal of Asthma and Allergy, 2022)
Albert C Chong,1 Kittipos Visitsunthorn,2 Peck Y Ong1– 3 1Keck School of Medicine, University of Southern California, Los Angeles, CA, USA; 2Department of Pediatrics, Children’s Hospital Los Angeles, Los Angeles, CA, USA; 3Division of Clinical Immunology and Allergy, Children’s Hospital Los Angeles, Los Angeles, CA, USACorrespondence: Peck Y Ong, Children’s Hospital Los Angeles, Division of Clinical Immunology and Allergy, 4650 Sunset Blvd., MS #75, Los Angeles, CA, 90027, USA, Tel +1323 361-2501, Email pyong@chla.usc.eduAbstract: Atopic dermatitis (AD) is one of the most common skin conditions in humans. AD affects up to 20% of children worldwide and results in morbidity for both patients and their caregivers. The basis of AD is an interplay between genetics and the environment characterized by immune dysregulation. A myriad of mutations that compromise the skin barrier and/or immune function have been linked to AD. Of these, filaggrin gene (FLG) mutations are the most evidenced. Many other mutations have been implicated in isolated studies that are often unreplicated, creating an archive of genes with potential but unconfirmed relevance to AD. Harnessing big data, polygenic risk scores (PRSs) and genome-wide association studies (GWAS) may provide a more practical strategy for identifying the genetic signatures of AD. Epigenetics may also play a role. Staphylococcus aureus is the most evidenced microbial contributor to AD. Cutaneous dysbiosis may result in over-colonization by pathogenic strains and aberrant skin immunity and inflammation. Aeroallergens, air pollution, and climate are other key environmental contributors to AD. The right climate and/or commensals may improve AD for some patients.Keywords: atopic dermatitis, genetics, environment, pollution